Kepemimpinan Transformasional Berbasis Pangadereng - Arisal Arisal (JURNAL MAPPESONA, 2023)
Transformational leadership is in line with the leadership model of the Bugis nation contained in the heritage of local wisdom of Pangadereng culture. Transformational leadership is a person's ability to arouse feelings, motivate and move others to do work in order to achieve organizational goals. Pangadereng is a culture that contains shared values and norms, is a social controller and regulates the behavior of everyone both for himself and his environment based on Lempue nasibawai tau, (honesty accompanied by piety), There is tongeng nasibawai tike, (truth of words accompanied by vigilance), Siri nasibawai getteng, (shame or self-esteem accompanied by determination), Awaraningeng nasibawai nyamengkininnawa, (courage accompanied by affection), Appesona ri Dewata Seuwae (surrender to God Almighty). Pangadereng-based transformational leadership places the basic values of lempuk, adatongeng, getteng, sipakatau and mappesona ri dewata seuwae, into the basis of amaccang. These values are called for and carried out in the form of pangadereng norms consisting of ade', talk, rapang, and wari'.